On the Other Side of Life - Brockhaus, Stefanie; Wolff, Andy (BR ; HFF ; ARRI Film & TV, 2010)
Coproduction: Germany, South Africa. Verzio FF Submission Duration: 01:27:00 Lucky and Bongani pretend to be cool and in the know. To survive in a Cape Town township, they learned their lessons early: where to get drugs, where to get money, how to pick up girls and how to get rid of them. The two brothers share everything: the bed, the food and now an accusation of murder. The first thing they get in prison is an unmistakable lesson about the rules there. No question, newcomers are always at the bottom of the hierarchy and they must learn quickly who may be attacked and who must be served. The two boys are initiated into the protocol of jailhouse life, however the real initiation comes after their grandma pays their bail: they undergo the more painful initiation of ritual circumcision. Caught between the gangster culture of the city and the spiritual traditions of the countryside, the pair grows more sympathetic while the details of their crime become more shocking. Through Lucky and Bongani’s story, the film becomes a far-ranging discourse about the future of Africa ground to pieces between tradition and modernity.